FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STATUS GIZI OBESITAS ORANG DEWASA DI KOTA DEPOK, TAHUN 2007 - ., Rahmawati; ., Sudikno (GIZI INDONESIA, 2008)
RISK FACTORS OF ADULT OBESITY IN DEPOK, WEST JAVA, IN 2007 There has been eating habit changes in big cities from consuming healthy food containingcomplex carbohydrate, and high fiber to junk food containing a lot of protein, fat, sugar, and saltbut little fiber and lack of physical activities will increase obesity. This study is an advance analysisof the risk factors of adult obesity and their characteristics in Depok. A cross-sectional study wasconducted to collect data from 366 samples, 176 men and 190 women aged 18-55 years old. Thesamples were selected using rapid assessment survey methodology. Percentage of adult obesitystatus (18-55 years old) is 16.4 percent, which is higher than the result of a study conducted in2004 (12.5 %). Percentage of women adult obesity status is higher than men. The women alsohave the risks of becoming obese 2.274 times higher than men. Percentage of adult obesity isdifferent across age group (p=0.044). The study showed that consuming deep fried food affectedobesity status (p= 0.010). Respondents who often consumed deep fried food had the risks ofbeing obese 2.337 times higher than those who rarely did that. In addition, it was found thatrespondents’ favorite food (deep fried food, fatty food, and food containing a lot of sugar) affectedtheir obesity status (p0.05). The analysis found the risks factors for adult obesity include age,sex, habits of consuming deep fried food, and favorite food (deep fried food, fatty food, and foodcontaining a lot of sugar).Keywords: adult, obesity, risk factors